Impact of Time Value of Money Theory in Ijarah Sukuk Genuineness; the Case of Bahrain and Malaysia - Sharif, Abdul Rahman; Abdullah, Adam (CCSE, 2018)
This research is a case study of two Ijarah Sukuk issuances in two countries. One issued by central bank of Bahrain and matured in 2014 and the other was issued by the Malaysian company TSH Resources Bhd and matured in 2017. By adopting library research and document analaysis, this research examines the terms and conditions of both cases based on what has been disclosed in the prospectuses. Accordingly, this study presents the impact of the Time Value of Money (TVM) in these cases and how it differentiates between genuine Ijarah Sukuk and a duplicate-bond Sukuk. The study revealed that there were some Shari’ah non-compliance issues in the implementation of Sukuk concept in both cases in a way it emulates conventional instruments featured as guaranteed-return instruments, which take into account TVM as an essential compenent in calculating its returns. However, such practice has a major effect on the genuineness of Sukuk, in terms of Shari’ah-compliance risk.